2005
DOI: 10.1063/1.2142075
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional photonic crystals based on porous n-type silicon

Abstract: Photonic crystals (PC) based on porous n-Si are fabricated and their structural, optical, and nonlinear optical properties are studied. The n-Si based PC composed of five pairs of layers with alternate porosity reveal a rather broad photonic band gap (PBG) of more than 100 nm and a reflectivity of up to 0.75. An average pore diameter of approximately 90 nm is found in n-Si based PC in contrast to mesoporous p-Si based PC, where pores are approximately 15 nm in diameter. Second-harmonic generation (SHG) spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Since the discovery of its luminescent properties in 1990, 1 the scientific and technological interest in porous silicon (PS) has been steadily increasing. Due to its unique properties PS is used in a wide variety of fields and applications, such as light emitting diodes, 2 photonic crystals, 3 biosensors 4 and gas sensors. 5 Many of these applications take advantage of PS's high surface area, which can be as much as 6 500 m 2 g À1 , depending on the fabrication conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of its luminescent properties in 1990, 1 the scientific and technological interest in porous silicon (PS) has been steadily increasing. Due to its unique properties PS is used in a wide variety of fields and applications, such as light emitting diodes, 2 photonic crystals, 3 biosensors 4 and gas sensors. 5 Many of these applications take advantage of PS's high surface area, which can be as much as 6 500 m 2 g À1 , depending on the fabrication conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary means for fulfilling the latter requirement rests on engineering the medium dispersion. PhC and MM have emerged as the most promising candidates for controlling the dispersion relations of the FF pump waves and SHG which could meet the QPM conditions [24–31]. The basic PhC structures with the necessary characteristics can be realized in the stratified medium with the periodic modulation of linear and nonlinear susceptibilities.…”
Section: Shg In 1‐d Artificial Mediamentioning
confidence: 99%
“…The latter phenomenon usually originates from the wave interference at the microscopic level, which leads to suppression of the propagating spatial harmonics and formation of the bandgaps. The nonlinear properties of multilayered PhC and MM have been investigated mainly in connection to improving the efficiency of frequency conversion and harmonic generation [24–109].…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies have indicated that nonlinear photonic crystals (PhCs) and metamaterials (MMs) have significant potential for enhancement of the nonlinear activity associated with the mechanisms of field confinement, dispersion management and resonant intensification of the interacting waves. For example, it has been demonstrated in [1][2][3][4][5] that the PhCs dispersion can be tailored to facilitate the phase synchronism (The phase synchronism between pump wave and its harmonic is a prerequisite for efficient frequency conversion.) between the second harmonic and the pump wave of fundamental frequency.…”
Section: Introductionmentioning
confidence: 99%